The application of composite materials in modern aviation and control of its condition during design service goal - A. V. Zibitsky; Yu. V. Stasyuk (Научный вестник МГТУ ГА, 2016)
This article has a purpose to give a brief review of usage of composite materials in the structure of modern civil aircraft. The current condition of civil aviation was analyzed, serious problems were determined and possible achievements in the future were discussed. Advantages and disadvantages of composite materials were analyzed, non-destructive methods of control were reviewed and the necessity to design new method, which allows to control the integrity of structure in real time during design service goal of the aircraft (the concept of “clever material”) was shown.